2021
DOI: 10.1186/s12886-021-02127-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 Pandemic on rhegmatogenous retinal detachment treatment patterns

Abstract: Backgrounds To describe changes in rhegmatogenous retinal detachment (RRD) surgical procedures in Beijing during the COVID-19 Pandemic. Methods A retrospective cohort of RRD patients was analyzed. Patients were divided into the COVID-19 pandemic group and pre-COVID-19 group according to their presentation. The presurgery characteristics, surgical procedures, and surgery outcomes were collected. The potential factors related to the choice of pars pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
1
5
1
Order By: Relevance
“…This study indicates that the proportion of scleral buckling (SB) was the highest at the beginning of the pandemic (42.9% in epidemic 1). This observation contradicts a previous report that surgeons encountered more complicated cases and preferred PPV over SB during the COVID-19 pandemic [ 21 ]. Although our results may be coincidental given the small sample size, the increased rate of SB might be attributed to a decrease in the average age of patients with RRD visiting our hospital.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study indicates that the proportion of scleral buckling (SB) was the highest at the beginning of the pandemic (42.9% in epidemic 1). This observation contradicts a previous report that surgeons encountered more complicated cases and preferred PPV over SB during the COVID-19 pandemic [ 21 ]. Although our results may be coincidental given the small sample size, the increased rate of SB might be attributed to a decrease in the average age of patients with RRD visiting our hospital.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study confirms a significant delay by patients with RRD in presenting to hospitals among the COVID-19 pandemic group, as also reported in previous studies [ 16 , 21 ]. This delay may have been due to anxiety about exposure to the COVID-19 virus in a healthcare environment.…”
Section: Discussionsupporting
confidence: 92%
“…1 Although emergent care was permitted for rhegmatogenous retinal detachment (RRD), single-institution-based studies comparing historical experiences to the 2020 COVID-19 lockdown period found patients delayed seeking care, had higher incidences of macula-off detachment and baseline proliferative vitreoretinopathy (PVR), and worse best-correct visual acuity (BCVA) at initial presentation. 2 , 3 , 4 However, multicenter studies analyzing the change in practice patterns and longitudinal outcomes during the COVID-19 lockdown (‘during-lockdown’) and the period immediately after (‘post-lockdown’) remain lacking.…”
mentioning
confidence: 99%
“…The geographical distribution of the fellowship programs is shown in Figure 1 and Table S2 (Supporting Information 1), and the fellowship experiences are also shown in Table 1. The median (IQR) duration of fellowship training was 15 months (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Basic Demographicsmentioning
confidence: 99%
“…[14][15][16][17][18] Few studies have discussed surgical decision changes. 16,19,20 Li et al 19 observed an increase in the proportion of PPV conducted in Beijing, China, and attributed it to the more complicated cases (e.g., RRD with choroidal detachment) presented. In contrast, Mundae et al 16 observed an increase in SB in Minneapolis-Saint Paul, USA.…”
Section: Introductionmentioning
confidence: 99%